Peran Kewarganegaraan Dalam Penegakan Hukum : Perspektif Hukum Nasional dan Hukum Islam - Ashfiya Nur Atqiya; Ahmad Muhamad Mustain Nasoha; Auliya Azzahra; Muhammad Fikri Al Kautsar; Sabrina Nur Hafishah; Zaky Prinda Manggala (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2024)
This research examines the role of citizenship in law enforcement from the perspective of domestic and Islamic law, with a focus on cases in Indonesia. In the context of national law, citizenship reflects the legal relationship between individuals and the state, where citizens have the right and obligation to participate in the law enforcement process. Meanwhile, according to Islamic law, citizen participation is based on the principle of amar ma’ruf nahi munkar, which requires Muslim individuals to encourage good and prevent evil. This research employs a doctrinal legal methodology, which involves the process of identifying, analyzing, and interpreting legal principles, norms, and doctrines to address the issues at hand. The distinctive feature of this approach is its prescriptive nature, aiming to offer solutions or recommendations regarding legal problems. The methodological framework utilized is normative or doctrinal research, also referred to as library research. This type of research relies on canonical sources (doctrinal literature) and specifically involves the use of library materials such as journals, books, legal documents, religious texts, and other relevant sources. The research primarily focuses on examining and analyzing written sources to gain a comprehensive understanding of the legal issues being studied.The research results show that there are similarities in the basic concept of citizen participation. , implementation varies depending on the social, cultural and legal context. In Indonesia, the role of citizenship in law enforcement is influenced by political dynamics and public trust in legal institutions. This study recommends strengthening legal education, developing participatory technology and harmonizing national law with Islamic law as steps to strengthen the role of citizens in law enforcement. In this way, it is hoped that law enforcement can run more effectively, fairly and in accordance with the values held by society.